Growth performance of cleft grafted velvet apple (Diospyros discolor Willd.): Cleft grafting of velvet apple - Robbani, Mahbub; Sarker, Chitta Ranjan (South Asian Journal of Agriculture, 2023)
Velvet apple is usually propagated through seeds but seeded plants do not maintain its true-to-type quality. The present work was undertaken to study the fate of cleft grafting of five selected velvet apple genotypes during 2018 - 2019 at the Germplasm Center, Patuakhali Science and Technology University. The pot experiment was conducted in RCBD with two factors as scions and Days after Grafting (DAG) consisting of 10 replications of the scions. Scions from five promising mother plants were considered as treatments (Dumki-Dd-S1, Dumki-Dd-S2, Dumki-Dd-S3, Dumki-Dd-S4 and Mirzaganj-Dd-S5) and were cleft grafted on seedling rootstock of Dumki-Dd-R1. At 84 DAG, significant differences were observed among the scion treatments regarding the studied growth parameters. The days required to bud break varied significantly which ranged from 14 days (Dumki-Dd-S4) to 18 days (Mirzagonj-Dd-S5). The maximum length (54.30 cm) and diameter (2.00 cm) of rootstock were recorded in Mirzagonj-Dd-S5 at 84 DAG. However, maximum scion length (22.20 cm) and scion diameter (0.70 cm) were noted in Dumki-Dd-S1at 84DAG. The highest graft heights of Dumki-Dd-S2 (71.20 cm) and Mirzaganj-Dd-S5(71.50 cm) were statistically similar at84 DAG. Graft success was highest in Mirzagonj-Dd-S5(60.00%) followed by Dumki-Dd-S4 (40.00%) at 84 DAG. The maximum number of sprouted shoots (2.10) was counted in Dumki-Dd-S1, however, the highest length and diameter of sprouted shoot (7.1 cm and 0.66 cm, respectively) and maximum number of leaf (7.40 per graft) were found in Mirzaganj-Dd-S5during the study period. It could be concluded that, Mirzaganj-Dd-S5 and Dumki-Dd-R1showed the best stionic relationship for multiplication of velvet apple by cleft grafting. South Asian J. Agric., Vol. 9, No.1&2, 2022-‘23: 1-10